DEVELOPING THE OUTCOMES OF A BACCALAUREATE OF DENTAL SURGERY PROGRAMME - Khan, Junaid Sarfraz; Tabasum, Saima; Mukhtar, Osama; Iqbal, Maryam (Journal of Ayub Medical College Abbottabad, 2010)
Background: Curriculum broadly falls into two categories, prescriptive and outcome-based. In the prescriptive curricula emphasis is placed on teaching with generally little integration between subjects and across disciplines. Currently, universities in Pakistan are undergoing a cultural change in the curricular design in order to apply an outcome-based learning instead of prescriptive teaching. Regionally, the need for change was recognised on account of the vast body of evidence available internationally. In order to bring about a shift towards an outcome based curriculum in the 4-year BDS programme, we first need to specify the outcomes/traits that the dental health professionals should be able to demonstrate upon leaving the programme. This paper describes the process and outcome of arriving at the desired consensus through a series of workshops involving all stakeholders including students, community members, teaching faculty, programme directors and representatives of the dental health industry. Methods: A series of workshops were conducted between September 2009 to February 2010 in all of the 18 disciplines of basic and dental sciences individually and then collectively. A questionnaire sought responses from the participants regarding their perception about the status of the current BDS curriculum and their understanding of an outcome-based integrated curriculum, as well as whether such an integrated curriculum should be adopted or not? In the second half of the workshop through brainstorming and Delphi technique, the outcomes in terms of measurable traits that should be possessed by a graduate dental health professional entering community service were enlisted. The preand post-workshop questionnaire scores were entered into SPSS-16 and paired sample t-test as well as chi-square test were applied. Cron back alpha value of <0.05 was taken as statistically significant. Secondly, the outcomes developed in each workshop were entered into Ethnograph® and common outcomes of the 4-year BDS programme were extracted. Results: In total, 234 participants attended the workshop over a period of five months in 18 discipline-wise workshops and four integrated workshops involving faculty members of all disciplines. Results indicate clearly that the workshop resulted in an attitude shift of the participants and their perception of the current curriculum and the need and rationale for a move towards an outcome-based curriculum. The 30 outcomes identified were grouped under two categories namely ’˜clinical skills’ and ’˜professional behaviours’. Conclusion: Defining the final programme outcomes is only the initial step in developing an outcome-based, objective, integrated curriculum which will require considerable work in the future. Keywords: Baccalaureate of Dental Surgery, Punjab, outcome-based curriculum, learning objectives, competencies